2016
DOI: 10.1093/mnras/stw3051
|View full text |Cite
|
Sign up to set email alerts
|

Hunting for eclipses: high-speed observations of cataclysmic variables

Abstract: Additional information: Use policyThe full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 108 publications
(150 reference statements)
1
22
0
Order By: Relevance
“…5)3.6 CSS 0524+00 (CSS131106:052412+004148)Since the discovery of CSS 0524+00 by CRTS on 2013 Nov 6(Drake et al 2009), ample coverage shows evidence of multiple eclipses and outbursts. With evidence of eclipses,Hardy et al (2017) observed CSS 0524+00, finding a period of 0.17466647(±2) d. We find a period of 0.1747(±3) d, in agreement with that found byHardy et al (2017). Our average light curve, folded on the ephemeris HJD min = 2456651.4295(±3) + 0.1747(±3) E, is shown inFigure 1; and shows eclipse depths of around 1.2 mag.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…5)3.6 CSS 0524+00 (CSS131106:052412+004148)Since the discovery of CSS 0524+00 by CRTS on 2013 Nov 6(Drake et al 2009), ample coverage shows evidence of multiple eclipses and outbursts. With evidence of eclipses,Hardy et al (2017) observed CSS 0524+00, finding a period of 0.17466647(±2) d. We find a period of 0.1747(±3) d, in agreement with that found byHardy et al (2017). Our average light curve, folded on the ephemeris HJD min = 2456651.4295(±3) + 0.1747(±3) E, is shown inFigure 1; and shows eclipse depths of around 1.2 mag.…”
supporting
confidence: 84%
“…The CRTS light curve shows evidence of previous outbursts, as well as a possible superoutburst. Hardy et al (2017) observed CSS 2144+22, confirming no eclipses. Our average light curve is shown in Figure 6.…”
Section: Asassn-15lsmentioning
confidence: 69%
See 2 more Smart Citations
“…Data were also collected using ULTRASPEC (Dhillon et al 2014), a single-band photometer with a frame-transfer, electron-multiplying CCD and only 15 ms dead time per cycle, which is mounted on the 2.4 m Thai National Telescope (TNT). Most of the ULTRA-SPEC data were taken using a custom filter, KG5 , which has a broader band to allow for shorter exposure times given the smaller collecting area of this telescope (for more details on the KG5 band, see Hardy et al 2017). A further series of eclipses were observed using CHIMERA (Harding et al 2016), a 2-band photometer which uses frame-transfer, electron-multiplying CCDs to achieve 15 ms dead time, and is mounted on the Hale 200-inch (5.1 m) Telescope.…”
Section: Observationsmentioning
confidence: 99%